(untitled) (Revista "Boletín el Conuco", 2026)
This article analyzes income tax and complementary taxes imposed on Colombian holding companies based on their asset structures. To this end, a mixed-methods approach was used, combining a quantitative approach to characterize a sample of six companies with a qualitative approach based on interviews with three experts. The results show that asset planning is a valid strategy for tax management by Colombian holding companies, as it leverages the tax benefits provided by Colombian tax rules.